(untitled) (Journal of Plant Disease Sciences, 2018)
The effect of fungicides, chemical, oils, wax and bio-agent against postharvest pathogens of Nagpur mandarin was evaluated for their inhibitory effect in vitro. Cent per cent mycelial growth inhibition of Colletotrichum gloeosporioides, Penicillium digitatum and Trichoderma viride were recorded in Benomyl @ 0.05 % and Benomyl @ 0.05 % + Potassium sorbate @ 2% and Hydrogen peroxide @ 10 per cent. Hydrogen peroxide @ 10 per cent recorded maximum mycelial growth inhibition (87.90%) of Geotrichum candidum. Complete growth inhibition (100%) of Trichoderma viride was achieved in Carbendazim @ 0.1%. Carbendazim @ 0.1%, Benomyl @ 0.05%, and Hydrogen peroxide @ 10% checked the cent per cent mycelial growth of Aspergillus Niger. Carbendazim @ 0.1% inhibited the mycelial growth of the Colletotrichum gloeosporioides (64.07%). Saccharomyces cerevisiae 109 recorded maximum growth restriction of Geotrichum candidum (14.94%). Benomyl @ 0.05 per cent inhibited 64.81 per cent mycelial growth of Penicillium digitatum. Saccharomyces cerevisiae 109 cfu/ml restricted mycelial growth (25.43%) of Aspergillus Niger. Carbendazim @ 0.1 per cent was found superior in inhibiting the mycelial growth of Trichoderma viride (32.96%).